The Relationship between Automatic Negative Thoughts and Depression among a Sample of University of Nizwa Students - Basim Mohammad Aldahadha; Suad Mohamed Sulaiman (Sultan Qaboos University, 2012)
The purpose of this study was to investigate the relationship between the automatic thoughts and depression in light of gender, specialization, level of study, achievement and hours of internet-usage. The sample of this study consisted of 329 (101 males and 228 females). Two instruments were used to collect the data: the Automatic Thought Questionnaire (ATQ) and the Beck Depression Inventory- second edition. (BDI-II). The results showed a positive correlation between depression and ATQ (r = 0.8, p. < 0.001). There was a negative correlation between ATQ and depression among non-depressed students (r = -0.78, p  < 0.001). There were significant differences between male and female students (p  < 0.05) in favor of females in ATQ. There were significant differences between the levels of achievement in favor of students with excellent GPA. The results also showed that there were no significant differences (p  0.05) that related to other variables.